Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 2 - Derivatives - 2.4 Derivatives of Trigonometric Functions - 2.4 Exercises - Page 150: 22



Work Step by Step

Given: $y=(1+x) \cos x$ Apply product rule, we get $y'=\cos x-(1+x) \sin x$ At $(0, 1)$, we have $y'=\cos(0)-(1+0) \sin (0)=1$ so we have $m=y'=1$ Formula to tangent line is : $y=mx+b$ $y-y_1=m(x-x_1)$ At $(0, 1)$, we have $y-1=1(x-0)$ This implies $y=x+1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.